Transformations of glycerol into high-value-added chemical products: ketalization and esterification reactions - Pérez, Federico Martín (2023)
Biomass allows us to obtain energy and high-value-added compounds through the use of different physical and chemical processes. The glycerol obtained as a by-product in the synthesis of biodiesel is considered a biomass compound that has the potential to be used as a raw material to obtain different chemical products for industry. The development and growth of the biodiesel industry allows for the projection of glycerol biorefineries around these plants that efficiently and sustainably integrate the biodiesel production process together with the glycerol transformation processes. This work presents a review of the ketalization and esterification of glycerol to obtain solketal and acetylglycerols, which are considered products of high added value for the chemical and fuel industry. First, the general aspects and mechanisms of both reactions are presented, as well as the related chemical equilibrium concepts. Subsequently, the catalysts employed are described, classifying them according to their catalytic nature (zeolites, carbons, exchange resins, etc.). The reaction conditions used are also described, and the best results for each catalytic system are presented. In addition, stability studies and the main deactivation mechanisms are discussed. Finally, the work presents the kinetic models that have been formulated to date for some of these systems. It is expected that this review work will serve as a tool for the advancement of studies on the ketalization and esterification reactions that allow for the projection of biorefineries based on glycerol as a raw material.